Online Collaboration Tools in Education: Google Does Sample - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
The main purpose of this paper is to develop and integrate collaboration tools into an educational setting and examine the effect of online collaborative learning tools on students' academic performance. Synchronous and asynchronous techniques of online collaborative learning tools and different models are used for this paper. One technique focuses on creating work samples and sharing them with friends; the other focuses on correcting the samples that friends created. This research is quasi-experimental, and a final test-control group trial model was utilized. The working group for the research included one control and three experimental groups, all consisting of seventh-grade middle school students. The experiments were carried out by four collaborating student groups. One of the main findings of this paper is that the online collaborative tools can be an alternative to face-to-face collaboration. In addition, the paper demonstrates that the students who corrected the mistakes of others were more successful than the students that prepared samples; however, there is no statistical support for this outcome.
Keywords: Technology; Online Collaboration; Synchronous and Asynchronous Collaboration; Academic Performance